A Qualitative Analysis of Counseling and Nurse Practitioner Trainee Experiences Engaging with an Integrated Behavioral Health (IBH) Training - Alexander M Fields; Margaret Emerson; Stephanie Burge; Jill R. Reed; Therese L Mathews Ph.D., APRN, BCBA-D; Abby L Bjornsen (Teaching and Supervision in Counseling, 2025)
Integrated behavioral health (IBH) is recognized as the standard for holistic healthcare, addressing the intersection of mental and physical health. As IBH gains prominence, graduate healthcare programs must equip students with strategies to meet its demands. However, limited research exists on training methods that address diverse professional identities and the unique needs of graduate students. Our novel IBH training incorporates interprofessional education (IPE) through modules and simulations grounded in Bandura’s (2001) social cognitive theory. We explored the experiences of 12 counseling, family nurse practitioner, and psychiatric/mental health nurse practitioner students through focus groups. Through interpretative phenomenological analysis (IPA), we analyzed our participants’ responses and present five themes: (1) role of previous experiences and emotional reactions, (2) interprofessional education and teamwork, (3) identifying the potential of IBH, (4) aligning professional values and fit, and (5) feedback on the training. We provide implications for nursing and counseling educators and scholars as healthcare providers aim to prepare the workforce for IBH.
Keywords: integrated behavioral health; interprofessional education; counseling; nursing; social cognitive theory